Beta Model - Robin Matzner (University College London, 2022)
Trained MPNN model to infer throughput values from a optical network topology with nodes beteween 25 - 45. This model has been trained with the Beta training dataset also available in this data repository.
Keywords: 100507 Optical Networks and Systems